2022
DOI: 10.1037/ccp0000719
|View full text |Cite
|
Sign up to set email alerts
|

The relation between the working alliance on mental illness and criminal thinking among justice-involved people with co-occurring mental illness and substance use disorders.

Abstract: Objective: The therapeutic working alliance is an important factor in producing treatment change and positive therapeutic outcomes for people with mental illness, yet little is known about the working alliance's role in treatment change in people with mental illness that is justice involved. In addition to treating the mental illness symptoms of justice-involved people with mental illness, addressing factors known to predict criminal behavior (including criminal thinking) could optimize posttreatment outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 26 publications
4
3
0
Order By: Relevance
“…Results of Study 1 suggest the PICTS-SF offers a reliable and structurally consistent method for assessing criminal thinking. Using two measures of internal consistency, the current study’s evidence of the PICTS-SF’s reliability is consistent with reliabilities found in previous studies using the PICTS-SF (Batastini et al, 2019, 2020; Scanlon et al, 2022; Varghese et al, 2018). As hypothesized, the PICTS-SF GCT, PCT, and RCT subscales demonstrated discriminant validity with the MCAA Attitudes toward Violence and Antisocial Intent subscales, per significant, positive and moderate correlations.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Results of Study 1 suggest the PICTS-SF offers a reliable and structurally consistent method for assessing criminal thinking. Using two measures of internal consistency, the current study’s evidence of the PICTS-SF’s reliability is consistent with reliabilities found in previous studies using the PICTS-SF (Batastini et al, 2019, 2020; Scanlon et al, 2022; Varghese et al, 2018). As hypothesized, the PICTS-SF GCT, PCT, and RCT subscales demonstrated discriminant validity with the MCAA Attitudes toward Violence and Antisocial Intent subscales, per significant, positive and moderate correlations.…”
Section: Discussionsupporting
confidence: 89%
“…In Studies 1 and 2, we found evidence of the 35-item version of the PICTS-SF's internal consistency reliability, using both alpha and omega estimates, similar to that found in previous studies (Batastini et al, 2019(Batastini et al, , 2020Gaspar et al, 2019;Scanlon et al, 2022;Varghese et al, 2018). We also found evidence for discriminant validity with two measures of the similar but distinct construct of antisocial attitudes: the MCAA and CSS-M.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Although there is no direct evidence connecting working alliance with reduced recidivism rates in sex offender counseling, the reasoning that these factors are connected is based on the strong connections between working alliance and client outcomes in non‐offender counseling. Moreover, recent empirical data has highlighted the importance of empathy and therapeutic alliance in sex offender counseling from the perspective of sex offender counselors (Carrola, 2022), and more broad research on offender counseling has shown the impact of working alliance in reducing both criminal thinking and mental illness symptoms in justice‐involved clients (Scanlon et al., 2022).…”
mentioning
confidence: 99%